PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN - Iin Kartini; Dede Djuniardi; Amir Hamzah (Jurnal Riset Keuangan dan Akuntansi, 2020)
The purpose of this study was to analyze the influence of Institutional Ownership, Managerial Ownership, Independent Board of Commissioners, Board of Directors, and Audit Committee on Financial Performance. The object of this research is the banking companies listed on the Indonesia Stock Exchange for the 2015-2018 period. The sampling technique used in this study is non probability sampling. The sample method uses Purposive Sampling. The data analysis technique used is the classic assumption test, panel data regression analysis, coefficient of determination and hypothesis testing using the software eviews 9. The partial research results show that Institutional Ownership has positive and significant effect on Financial Performance, Managerial Ownership has positive and significant effect on Financial Performance, Independent Board of Commissioners has positive and significant effect on Financial Performance, Board of Directors has positive and significant effect on Financial Performance, Audit Committee influences positive and significant impact on financial performance. Keywords: Institutional Ownership, Managerial Ownership, Independent Board of Commissioners, Board of Directors, and Audit Committee